Comparative Analysis of Real-time and Conventional Overall Equipment Effectiveness Applications in Manufacturing Industry - Susilawati, Anita; Yohanes, Yohanes; Putri, Sunny Ineza; Prasetyo, Brian Agung Cahyo; Saputri, Anggraini Dwi; Ihsan, Yaser (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Overall Equipment Effectiveness (OEE) is a comprehensive measure to identify the level of productivity and performance of machines/equipments. Conventional approaches to OEE data processing, such as using Microsoft Excel, have limitations. Consequently, the data processing process becomes less efficient and prone to human error. This study aims to examine the application of OEE in the Manufacturing Industry, measurable performance gaps between conventional and real-time approaches. The methodology used in this study was based on a synthetic literature review to evaluate the effectiveness of both OEE approaches based on existing studies. The transition of OEE from mere calculations to dynamic, real-time, and integrated systems is a direct response to the increasing complexity and competitiveness of the modern manufacturing environment. This study can be used to identify areas for future development and as a reference for further research to provide a guide to OEE practitioners in implementing improvements.